HKICEPS-3678 exploring the motivation for and barriers to academic leadership among Malaysian polytechnic lecturers of FELDA settlement background - Robani, Anidah; Dora, Mohd Taib; Syed Hassan, Syed Najmuddin; Hussin, Hanipah; Husain, Kalthom; Md Saad, Mohd Shamsuri; Zainudin, Mohamad Zahir; Mohd Idris, Mohd Fadzil (2013)
This paper reports findings of a study on motivation for and barriers to effective academic leadership among Malaysian polytechnic lecturers on FELDA settlement background. In general, this study is to examine the academic leadership potential among Malaysian polytehcnic lecturers notably in the field of teaching and learning, research and innovation, academic writing, consultation as well as community services. Specifically, this study aims at exploring the motivation for and barriers to effective academic leadership among Malaysia polytechnic lecturers of FELDA settlement background. To achieve the objectives of this study, in-depth focused group interviews were conducted among 45 respondents. The respondents were selected based on the analysis done during the quantitative stage. The study found that motivation for effective academic leadership can be grouped under three main themes; (i) the organizational and managerial issues, (ii) organizational culture and environment, (iii) personal experience and quality issues. Furthermore, the study has identified personal and family issues as the main barriers to effective academic leadership among Malaysian polytechnic lecturers. The findings are useful to the Department of Polytechnic Education, Ministry of Education, Malaysia. These findings show the need to equip its lecturers, particularly in academic leadership, so that the polytechnic lecturers are competent enough to actualize the transformation agenda of the Malaysia Higher Education. Further implications on FELDA in transforming its human capital are also discussed in the final section of this paper.